O cuidado de enfermagem para com o ser que vivencia uma complicação podológica, decorrente do Diabetes Mellitus: um enfoque fenomenológico - Moreira, Ricardo Castanho (2007)
Current research hails from the author's experience shared with diabetic persons. Experience revealed the paradox between the dimension of the individual's existential needs and the care provided by the health team. This fact triggered a new phenomenon, or rather, to existentially understand the sick persons with Diabetes Mellitus-caused podological complications and to rethink other care possibilities. Heidegger's existential phenomenology made possible the understanding of certain events experienced by the above-mentioned individuals. Eight persons with diabetes-caused podological complications, living in the northern region of the state of Paraná, Brazil, were interviewed between February and August 2007, in their own homes. The following fundamental question was made to the subjects involved: How are you coping with a podological complication caused by diabetes mellitus? Vicissitudes experienced by the subjects with podological complication in their daily lives were perceived through the recording of body reactions and silences. Interpretation of interviewed people's affidavits on their feelings comprised the following three groups: being-in-the-world and non-authentic care; being-in-the-world and concern on the future; being-in-the-world and authentic care. The above existential themes expressed the experience of people with diabetes with foot lesions and unveiled a future with human needs and necessities. Results show the importance of holistic care to the human being with such experience, since subjectivity is frequently erased by the pressure of institutional rules and norms. Their need is not merely to take care of foot lesions but to transcend the physical stance and attend to the entire existential necessities of the subject, respecting his/her historicity and sharing each and every decision taken.